Surface treatment effects on bond strength of CAD/CAM fabricated posts to root canal dentin - Oğuz Ahmet, Serra; E?ilmez, Ferhan; Ergün, Gülfem; Çekiç-Nagaş, Işıl (Mosher and Linder, Inc, 2019)
Purpose: To compare the effect of different surface treatments on the bond strength of CAD/CAM fabricated resin-based and prefabricated fiber posts to root canal dentin. Methods: 160 single-rooted human teeth were selected and received endodontic treatment. The teeth were divided into four groups according to the post material used: (1) Prefabricated fiber-reinforced composite post (Snowpost), (2) CAD/CAM nanoceramic (Cerasmart), (3) CAD/CAM polymer infiltrated ceramic (Vita Enamic) and (4) CAD/CAM resin nanoceramic (Lava Ultimate). Then the posts were randomly assigned into four sub-groups according to the surface treatment method used: (1) Control (no treatment), (2) Laser (Er,Cr:YSGG laser device, Waterlase), (3) Hydrofluoric acid treatment [9.6% HF (Pulpdent) for 2 minutes], and (4) Sandblasting (50 urn AI2O3). Following post space preparation, posts were cemented with dual-cure resin cement (Panavia SA cement plus). From each root, five 1 mm-thick slices were obtained. The micropush-out bond strength test was performed for each slice. Data were analyzed by using two-way ANOVA and Tukey HSD tests. The fracture modes were evaluated under a stereomicroscope. Representative specimens were analyzed with SEM following surface treatments. Results: Micropush-out bond strength of posts to dentin was significantly affected by the type of post material (P< 0.05), but not by the surface treatment (P= 0.397).
Keywords: Fiber Posts; Glass-Fiber; Self-Adhesive; Resin Cements